Rancangan Aplikasi Paket Pelaminan Online di Kota Batam - Alvendo Wahyu Aranski; Rahmat Fauzi (Journal of Information System and Technology (JOINT), 2020)
Marriagee is something that is very desirable every prospective partner in life. Everyone wants a luxurious and good marriage because it's only once in a lifetime. Marriage is considered a sacred activity so it needs to be planned well and carefully. Not only the two people who will be tied with a wedding rope that needs to be prepared, the preparation of the wedding party must also be considered as well as possible. The main thing that becomes a supporter of a wedding is the aisle. With the selection of a good aisle, a wedding will look luxurious and classy. Not a few couples who are disappointed with the wedding package that has been chosen. This is caused by the ignorance of the bride and groom in determining the existing wedding package. Disappointment of prospective brides in choosing a wedding package is the lack of information on existing packages. They don't know much about the various types of wedding packages available. Most of what they know is only the type of tent that will be used, even though the aisle package isn't just that. Android-based application design, determining the selection and ordering of a wedding package in the city of Batam will be able to answer the confusion of the bride and groom.